Optimalisasi Pengelolaan Dana Pendidikan Di SD Negeri 5 Nisam Sebagai Upaya Peningkatan Kualitas Pembelajaran - Nurhafni; Yusra; Sonny Muhammad Ikhsan Mangkuwinata (Program Studi Pendidikan Agama Islam, 2026)
Ideally, educational fund management should be effective, transparent, accountable, and participatory. However, obstacles such as delays in the disbursement of School Operational Assistance (BOS) funds and low stakeholder participation are still frequently encountered in elementary schools. This study aims to analyze the optimization of educational fund management at SD Negeri 5 Nisam as an effort to improve learning quality. The novelty of this research lies in the analysis of optimization strategies directed at enhancing stakeholder participation, management transparency, and budget allocation based on school priority needs. Employing a mixed-methods approach, data were collected through interviews, observations, documentation, and questionnaires distributed to teachers and parents. The results indicate that educational fund management at SD Negeri 5 Nisam has been implemented fairly well through a systematic organizational structure based on the School Activity and Budget Plan (RKAS). Fund optimization has a positive impact on improving learning facilities and the quality of the teaching-learning process, although challenges remain regarding community participation and the stability of BOS fund distribution.